Traffic and Random Processes: An Introduction - Mauro, Raffaele (Springer, 2016)
This book deals in a basic and systematic manner with the fundamentals of random function theory and looks at some aspects related to arrival, vehicle headway and operational speed processes at the same time. The work serves as a useful practical and educational tool and aims at providing stimulus and motivation to investigate issues of such a strong applicative interest. It has a clearly discursive and concise structure, in which numerical examples are given to clarify the applications of the suggested theoretical model. Some statistical characterizations are fully developed in order to illustrate the peculiarities of specific modeling approaches; finally, there is a useful bibliography for in-depth thematic analysis.